A Wide Bandgap Halide Perovskite Based Self‐Powered Blue Photodetector with 84.9% of External Quantum Efficiency. Issue 51 (14th November 2022) - Yun, Yeonghun; Han, Gill Sang; Park, Gyu Na; Kim, Jihyun; Park, Jinhong; Vidyasagar, Devthade; Jung, Jina; Choi, Won Chang; Choi, Young Jin; Heo, Kwang; Kang, Joohoon; Park, Ji‐Sang; et al.
Abstract: A self‐powered, color‐filter‐free blue photodetector (PD) based on halide perovskites is reported. A high external quantum efficiency (EQE) of 84.9%, which is the highest reported EQE in blue PDs, is achieved by engineering the A‐site monovalent cations of wide‐bandgap perovskites. The optimized composition of formamidinium (FA)/methylammonium (MA) increases the heat of formation, yielding a uniform and smooth film. The incorporation of Cs + ions into the FA/MA composition suppresses the trap density and increases charge‐carrier mobility, yielding the highest average EQE of 77.4%, responsivity of 0.280 A W −1, and detectivity of 5.08 × 10 12 Jones under blue light. Furthermore, Cs + improves durability under repetitive operations and ambient atmosphere. The proposed device exhibits peak responsivity of 0.307 A W −1, which is higher than that of the commercial InGaN‐based blue PD (0.289 A W −1 ). This study will promote the development of next‐generation image sensors with vertically stacked perovskite PDs. Abstract : A high‐performance and self‐powered blue perovskite photodetector (PPD) is developed by designing and optimizing A‐site of APb(Br0.65 Cl0.35 )3 (A = formamidinium (FA + ), methylammonium (MA + ), Cs + ) perovskites (PVSKs). The incorporation of Cs + into FA/MA‐PVSKs reduces the lattice strain and defect density. Consequently, a best‐performing Cs‐incorporating device shows an external quantum efficiency (EQE) of 84.9% which is the highest EQE reported in blue PDs.